Counseling on Communication Ethics Through Electronic Media to the Saham Longhouse Community in Landak Regency - Gatot Yuliana; Regina Regina; Sudarsono Sudarsono; Ikhsanudin Ikhsanudin; Clarry Sada; Dwi Riyanti; Y. Touvan Juni Samodra (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The community service entitled "Counseling on the Ethics of Communication through Electronic Media to the Rumah Panjang Saham Community, Landak District" aims to provide electronic media and social media. The use of cell phones and the internet has now penetrated not only urban areas but also rural areas and even remote areas as long as there is a signal and an internet network. The PKM was carried out by the Dedication Team for the English Language Education Masters Study Program, FKIP, Tanjungpura University, Pontianak, at the Saham Long House, Saham Village, Sengah Temila District, Landak Regency, on Thursday, September 8, 2022, from 17:00–21:30, and was attended by 52 participants. Activities run well and smoothly. The participants enthusiastically took part in the activity. From the results of the discussion, it could be concluded that the activity was very useful for them, and they hoped that similar activities could be carried out again.